Robotics technology in car seat polyurethane injection process for small and medium size industries in Malaysia / Syairul Izam Ab Ghani and Mohd Shuhidan Saleh - Ab Ghani, Syairul Izam; Saleh, Mohd Shuhidan (2004)
At Rokisar Sdn. Bhd. the method and technique of car seat Polyurethane (P/U) injection process is still done manually. The project of our study is on improving the car seat Polyurethane Injection process at Rokisar Sdn. Bhd. The focus is base on implementing the use of Robot's arms as a new techniques or method in the injection processes. The Quest Simulation Software is used to create the simulation for Robot's arms movement for the automated processes. In this project, work-study method will be adopted as a means of developing the new technology of P/U injection process. The work study method and techniques encapsulating the overall improvement method and technology development as well as associated management issues.